CRISPR‐Cas9 Genome Editing of Primary Human Vascular Cells In Vitro. Issue 11 (8th November 2021) - Atri, Deepak S.; Lee‐Kim, Vivian S.; Vellarikkal, Shamsudheen K.; Sias‐Garcia, Oscar; Yanamandala, Mounica; Schniztler, Gavin R.; Gupta, Rajat M.
Abstract: Genome editing of primary human cells with CRISPR‐Cas9 is a powerful tool to study gene function. For many cell types, there are efficient protocols for editing with optimized plasmids for Cas9 and sgRNA expression. Vascular cells, however, remain refractory to plasmid‐based delivery of CRISPR machinery for in vitro genome editing due to low transfection efficiency, poor expression of the Cas9 machinery, and toxic effects of the selection antibiotics. Here, we describe a method for high‐efficiency editing of primary human vascular cells in vitro using nucleofection for direct delivery of sgRNA:Cas9‐NLS ribonucleoprotein complexes. This method is more rapid and its high editing efficiency eliminates the need for additional selection steps. The edited cells can be employed in diverse applications, such as gene expression measurement or functional assays to assess various genetic perturbation effects in vitro . This method proves effective in vascular cells that are refractory to standard genome manipulation techniques using viral plasmid delivery. We anticipate that this technique will be applied to other non‐vascular cell types that face similar barriers to efficient genome editing. © 2021 Wiley Periodicals LLC. Basic Protocol : CRISPR‐Cas9 genome editing of primary human vascular cells in vitro